Therapeutic Outcomes and Risk Factors for Complications of Endoscopic Papillectomy: A Retrospective Analysis of a Single-Center Study - Jiang L; Chai N; Li M; Linghu E (Dove Medical Press, 2021)
Lei Jiang,1,2,* Ningli Chai,1,2,* Mingyan Li,2 Enqiang Linghu1,2 1School of Medicine, Nankai University, Tianjin, 300071, People’s Republic of China; 2Department of Gastroenterology and Hepatology, First Medical Center of Chinese PLA General Hospital and Chinese PLA Medical College, Beijing, 100853, People’s Republic of China*These authors contributed equally to this workCorrespondence: Enqiang LinghuDepartment of Gastroenterology and Hepatology, First Medical Center of Chinese PLA General Hospital and Chinese PLA Medical College, No. 28 Fuxing Road, Haidian District, Beijing, 100853, People’s Republic of ChinaTel +86 10 6818 2255- 499292(o)Fax +86 10 68154653; +86 10 55499292Email linghuenqiang@vip.sina.comPurpose: Endoscopic papillectomy (EP) has been accepted as a viable alternative therapy to surgery in benign duodenal papillary lesions. However, postoperative complications limit its widespread clinical application. This study aimed to evaluate the overall safety of the EP procedure and identify significant risk factors of post-EP complications.Patients and Methods: We retrospectively collected 76 patients who had undergone EP in Chinese PLA General Hospital from 2016 to 2019 and graded their postoperative complications. We assessed twelve patient-, disease- or procedure-related variables to identify risk factors related to the occurrence of post-EP complications using both univariate and multivariate analyses.Results: Among the 76 patients included in this study, the incidence of entire post-EP complications was 36.8%, most of which were in a mild form. In both univariate and multivariate analyses, the pathologic tumor types, especially high-grade intraepithelial neoplasia (HIN), and the placement of stents were significantly associated with the occurrence of post-EP complications. Patients with HIN tumors were more likely to have post-EP pancreatitis, bleeding, and overall complications (odds ratio (OR) 11.66, 95% confidence interval (CI) 2.91– 62.5, P = 0.001; OR 6.52, 95% CI 1.45– 46.77, P = 0.027; OR 9.81, 95% CI 2.75– 44.04, P = 0.001, respectively). Pancreatic stent placement may contribute to the occurrence of post-EP pancreatitis (OR 7.61, 95% CI 1.37– 64.53, P = 0.033). While biliary stent placement was found negatively related to the occurrence of post-EP bleeding and overall complications (OR 0.02, 95% CI 0– 0.37, P = 0.016; OR 0.11, 95% CI 0.01– 0.99, P = 0.05, respectively).Conclusion: EP is a safe procedure for papillary lesion treatment with a low rate and generally mild postoperative complications. Two factors are significantly associated with the occurrence of complications. The selection of eligible patients and suitable procedures is important to reduce the complication rate and severity.Keywords: duodenal papillary lesion, endoscopic papillectomy, complications, risk factors